Evaluating The Electrochemical Performance Of Graphite And Silicon-Based Materials In Energy Storage Device - Pawan D. Somavanshi; Yogesh U. Sathe (Revista Electronica de Veterinaria, 2023)
Sodium-ion batteries (SIBs) have emerged as a promising alternative to lithium-ion batteries (LIBs) since sodium resources are more abundant, and their utilization is cheaper. However, their application is limited by the problem of obtaining high energy density and stable cycling in the long term. In the following study, we discuss usage of silicon dioxide (SiO₂) and graphene oxide (GO) to overcome these issues. Comparative Cyclic voltammetry, Galv. current density, energy density and capacity density measurement between pure GO, SiO₂ and GO-SiO₂ composites for SIB configurations. GO was found to have good conductivity and improved Na-ion transport but cycling stability was moderate. SiO₂ showed ordinary cycling stability but lower initial capacity as compared to the composite material. The incorporation of SiO₂ in the structure of the GO material has a synergistic effect where both the GO high conductivity and the structure stability of SiO₂ and therefore improved sodium-ion storage capability and long-term cycling stability. From these conclusions, it can be proposed that GO-SiO 2 composites can be promising materials for practical applications of SIBs as an efficient anode with sufficiently high capacity and conductivity.